Cypermethrin Inhalation Induced Renal Lesions in Albino Rats - Khalequzzaman, M; Saha, AK; Begum, R (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Pyrethroid; kidney; creatinine; histopathology; ratBangladesh j. genet. biotechnol. 5 (1&2): 69-72, 2004 (June & December)